The media discourse in the press digital basketball male and female in Huelva - De Casas-Moreno, P.; Rodríguez-Vázquez, F. M.; Aguaded, I. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The present research focuses on the study of the transformation of journalistic discourse through a semantic analysis and interpretative hermeneutic units collected, in response to a study quanti-qualitative of topics and the most repeated rhetorical figures found in the news of the digital press of Huelva. The power of the media in shaping public opinion and the construction of reality generated a constant debate on the form of drafting the journalistic information. Gender differences, as well as the positive and negative aspects in the League masculine and feminine basketball cause the address information in the digital press to become an element of analysis. The results obtained show that the digital press of Huelva, bet for the prayers and positive codes at the time of informing about the male and female teams analyzed.